Research on property income inequality effect of fiscal finance - Xiaozhun Peng; Hongyou Lu (Economies, 2020)
"Creating conditions for more people to have property income" has become a national policy after the 17th National Congress of the Communist Party of China. Based on the micro survey data from Chinese Family Panel Studies (CFPS) in 2010, 2012, 2014, 2016 and the macro panel data at the provincial level, a logarithmic linear equation was built to estimate the impact of micro and macro factors on property income. Furthermore, the contribution of fiscal expenditure and financial development on property income equality can be recognized using the regression-based inequality decomposition method. This research revealed that fiscal expenditure improves residents' property income and slightly reduces the inequality of property income distribution. With respect to financial development, it improves residents' property income but aggravates the inequality of property income distribution. However, there is a significant difference between the different regions. In eastern and central regions, inequality of property income distribution greatly benefits from fiscal expenditure, while in northwest regions, fiscal expenditure makes property income inequality even worse. Therefore, the focus of financial sustainable development is to reduce property income inequality through the establishment of an effective government and the improvement of the rule of laws.
Keywords: G10; H30; E6; 330; financial development; fiscal expenditure; fiscal redistribution; property income